Growth, Technological Interdependence and Spatial Externalities - Theory and Evidence - Cem Ertur; Wilfried Koch (European Regional Science Association (ERSA), 2005)
This paper presents a theoretical model, based on the neoclassical growth literature, which explicitly takes into account technological interdependence among economies and examines the impact of location and neighborhood effects in explaining growth. Technological interdependence is supposed working through spatial externalities. The magnitude of the physical capital externalities at steady state, which is usually not identified in the literature, is estimated using a spatial econometric specification explaining the steady state income level. This spatially augmented Solow model yields a conditional convergence equation which is characterized by parameter heterogeneity. A locally linear spatial autoregressive specification is then estimated.
Keywords: 330